10.5k views
4 votes
Calculate ------ please

Calculate ------ please-example-1
User MistaPrime
by
5.3k points

2 Answers

3 votes

Answer:

6

Explanation:


\frac{\sqrt{(5+√(11))^(2) + (5-√(11))^(2)}}{√(2) } = \frac{\sqrt{25 + 10√(11) + 11 + 25 - 10√(11) + 11}}{√(2) } = (√(72))/(√(2) ) = (√(72) * √(2) )/(√(2) * √(2) ) = (√(144) )/(2) = (12)/(2) = 6

User Ambussh
by
5.6k points
1 vote

Answer:

The answer is 6

Explanation:

I calculated the answer using a calculator.

User JShorthouse
by
5.8k points